2004
DOI: 10.1097/00054725-200407000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Transabdominal Ultrasonography and Magnetic Resonance Imaging in Patients With Inflammatory Bowel Disease of the Terminal Ileum and Large Bowel

Abstract: This study provides strong evidence that US should be considered as a first-choice method for follow-up of patients with IBD of the terminal ileum and large bowel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 53 publications
4
90
0
12
Order By: Relevance
“…MRE is very precise in determining the location and extension of the inflammatory lesions (sensitivity 74%, specificity 91%) in CD (5), which is very close to the precision demonstrated by CT enterography (18) and greater than the precision of ultrasound for locations in the jejunum and proximal ileum (19). In our series, the majority of the patients in whom an extension study was performed using MRE, disease activity was found in the jejunum and proximal ileum which led to a change in the therapeutic management of these patients due to having extensive disease.…”
Section: Discussionmentioning
confidence: 63%
“…MRE is very precise in determining the location and extension of the inflammatory lesions (sensitivity 74%, specificity 91%) in CD (5), which is very close to the precision demonstrated by CT enterography (18) and greater than the precision of ultrasound for locations in the jejunum and proximal ileum (19). In our series, the majority of the patients in whom an extension study was performed using MRE, disease activity was found in the jejunum and proximal ileum which led to a change in the therapeutic management of these patients due to having extensive disease.…”
Section: Discussionmentioning
confidence: 63%
“…Transabdominal ultrasound is a simple and noninvasive procedure, and the measured bowel wall thickness is known to correlate with degree of inflammation (4)(5)(6). Although it has been reported that bowel wall thickness decreases early as the disease improves, the decrease rate of an early wall thickening has been studied, whether or not the decrement of colonic wall thickness can predict the response to CAP therapy has not been published.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed a good comparability between the results of MRE and ultrasound, in some ultrasound was even superior [12,13,14,20]. Others suggested that MRE was superior to ultrasound, particularly regarding the localization of affected bowel segments and the detection of fistulas [11].…”
Section: Discussionmentioning
confidence: 99%
“…Some suggest MRE to be superior to ultrasound, particularly regarding the localization of affected bowel segments and the detection of fistulas [11]. Other studies showed a good comparability between the results of MR enterography and ultrasound [12,13,14]. …”
Section: Introductionmentioning
confidence: 99%